Biometric statehood, transnational solutionism and security devices: The performative dimensions of the IOM’s MIDAS - Singler, Samuel (Theoretical criminology, 2021)
This article contributes to border criminology and transnational criminal justice research into the role of transnational actors in shaping practices of global justice, punishment and control, as well as to the criminological analysis of penal technologies. I examine the performative effects of the Migration Information and Data Analysis System (MIDAS) developed by the International Organization for Migration (IOM), and I argue that these effects are multidimensional. For beneficiary states, the deployment of MIDAS constitutes a performance of sovereign territorial power, affirming membership in the international society of (biometrically capable) states. For the IOM, the development and deployment of MIDAS and carrying out training sessions operate as pedagogical interventions legitimizing the organization as a neutral, technical expert of migration management. Finally, MIDAS itself performatively acts upon its targets, constituting ‘the migrant’ as a governable, potentially risky subject and constituting ‘migration’ as a problem amenable to depoliticized techno-solutionist interventions.